SISTEM INFORMASI KESEHATAN IBU HAMIL BERBASIS ANDROID DI BIDAN PRAKTIK MANDIRI TAWANGSARI SUKOHARJO - Maulita, Yunia Rahma; Fitriasih, Sri Hariyati; Irawati, Tri (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2024)
Based on data obtained from the Sukoharjo District Health Office in 2021, the Maternal Mortality Rate is 0.17%. The death of a pregnant woman is caused by uterine rupture and amniotic embolism, ekalamsi, hypovolemic shock, hepaomegaly. While the Infant Mortality Rate in Sukoharjo Regency in 2021 was 3.88%. The biggest cause of infant death is because the baby is born prematurely with a low birth weight baby (Dinkes, 2018). In the Independent Practice Midwife (BPM) Ponirah Tawangsari Sukoharjo, only a few pregnant women know the knowledge of pregnancy and babies because of the lack of information facilities used. In addition, because of the limited time mothers can not tell their complaints in full to the health workers, so there are still many mothers who are confused and less quick to take action due to lack of knowledge. The method used in developing this application is to use the RAD (Rapid Application Development) method. While the construction uses the Kotlin and XML programming languages with Android Studio software. This application is divided into 2 namely applications for midwives and pregnant women. Android-based maternal health applications consist of the process of managing patient data, examination data, complaint data, fetal development data, health check features and HPL (Estimated Birth Day) with the aim of providing information about the health of pregnant women during pregnancy